OZIQ - OVQAT XAVFSIZLIGINING DOLZARB MUAMMOLARIGA DOIR - Sharopova, Mohidil; Zubaydova, Zamira (MODERN PROBLEMS AND PROSPECTS FOR ORGANIZING A HEALTHY LIFESTYLE AND PROPER NUTRITION, 2024)
OZIQ - OVQAT XAVFSIZLIGINING DOLZARB MUAMMOLARIGA DOIR